Three-Dimensional Human Cell Culture Models to Study the Pathophysiology of the Anterior Eye - García-Posadas, Laura (Pharmaceutics, 2020)
In recent decades, the establishment of complex three-dimensional (3D) models of tissues has allowed researchers to perform high-quality studies and to not only advance knowledge of the physiology of these tissues but also mimic pathological conditions to test novel therapeutic strategies. The main advantage of 3D models is that they recapitulate the spatial architecture of tissues and thereby provide more physiologically relevant information. The eye is an extremely complex organ that comprises a large variety of highly heterogeneous tissues that are divided into two asymmetrical portions: the anterior and posterior segments. The anterior segment consists of the cornea, conjunctiva, iris, ciliary body, sclera, aqueous humor, and the lens. Different diseases in these tissues can have devastating effects. To study these pathologies and develop new treatments, the use of cell culture models is instrumental, and the better the model, the more relevant the results. Thus, the development of sophisticated 3D models of ocular tissues is a significant challenge with enormous potential. In this review, we present a comprehensive overview of the latest advances in the development of 3D in vitro models of the anterior segment of the eye, with a special focus on those that use human primary cells.